2014
DOI: 10.2971/jeos.2014.14038
|View full text |Cite
|
Sign up to set email alerts
|

Study on the temperature field loaded by a shaped laser beam on the top surface of a cylinder head for thermal fatigue test

Abstract: In thermal fatigue test, the key point is whether the temperature field on the top surface of cylinder head induced by the heat source can well match it in real service. In order to produce the target temperature field in service which is measured by thermocouples, shaped laser beam generated by diffractive optics element (DOE) is chosen as the heat source to irradiate on the top surface of cylinder head. The DOE is designed based on the Gerchberg-Saxton (GS) algorithm and the simulated temperature field is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Because of the ability to freely modulate the irradiance and phase profile of laser beam by the surface relief microstructure, diffractive optical elements (DOEs) have been widely used in laser beam shaping technology [7][8][9][10]. Based on the spatial shaping technology and DOE, some studies [11][12] have shown that, in thermal fatigue test of engine parts, it is possible to use a shaped laser beam for thermal loading to induce temperature field similar to the actual working condition. The spatial intensity distribution of the shaped laser beam can be modulated according to the temperature value of each position, so as to ensure the accuracy and reliability of thermal fatigue test.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the ability to freely modulate the irradiance and phase profile of laser beam by the surface relief microstructure, diffractive optical elements (DOEs) have been widely used in laser beam shaping technology [7][8][9][10]. Based on the spatial shaping technology and DOE, some studies [11][12] have shown that, in thermal fatigue test of engine parts, it is possible to use a shaped laser beam for thermal loading to induce temperature field similar to the actual working condition. The spatial intensity distribution of the shaped laser beam can be modulated according to the temperature value of each position, so as to ensure the accuracy and reliability of thermal fatigue test.…”
Section: Introductionmentioning
confidence: 99%